2014
DOI: 10.1016/j.sbspro.2014.11.079
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Threat of Punishment on Tax Compliance and Non-compliance Attitudes in Malaysia

Abstract: Threat of punishment has been emphasized as one of the effective tools to deter taxpayers' non-compliance attitudes. Thus this study aims to explore the impact of threat of punishment on both individual taxpayers' attitudes, compliance and noncompliance. The findings from a mixed-modes survey indicate that threat of punishment is insignificant on taxpayers who are willing to comply with tax laws. They tend to avoid taxes when they are threatened with tax audits and penalties. Overall, threat of punishment appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 23 publications
3
26
0
6
Order By: Relevance
“…On the other hand they tend to avoid taxes when they are threatened with tax audits and penalties. Their willingness to comply perhaps deteriorates as they are being threatened for things that they do not have any intentions to do (Mohdali, Isa, & Yusoff, 2014). ast studies found that, even though tax evasion was generally considered to be unethical, there were exceptions.…”
Section: Tax Compliance Behaviourmentioning
confidence: 99%
“…On the other hand they tend to avoid taxes when they are threatened with tax audits and penalties. Their willingness to comply perhaps deteriorates as they are being threatened for things that they do not have any intentions to do (Mohdali, Isa, & Yusoff, 2014). ast studies found that, even though tax evasion was generally considered to be unethical, there were exceptions.…”
Section: Tax Compliance Behaviourmentioning
confidence: 99%
“…Taxpayer compliance has a critical value because if there is incompliance, it will also trigger an attempt to avoid tax which will decrease the revenue for the state treasury. Mohdali et al, (2014) in his research showed that giving penalties had a significant positive effect on tax compliance. Penalties can prevent tax avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…Penegakan kepatuhan dengan ancaman hukuman tidak berdampak signifikan terhadap wajib pajak yang mempunyai niat untuk patuh, tetapi justru memicu niat untuk kurang patuh. Ancaman hukuman cocok untuk meningkatkan kepatuhan WP yang tidak patuh (Hunt & Iyer, 2018;Jimenez & Iyer, 2016;Mohdali, Isa, & Yusoff, 2014). Oleh karena itu, gabungan yang tepat dari instrumen kebijakan pencegahan untuk menekan penghindaran pajak bergantung pada moralitas wajib pajak.…”
Section: Gambar 3 Modifikasi Fischer's Modelsunclassified
“…Pendapat tersebut didukung oleh sekelompok psikolog sosial, bahwa dalam kondisi tertentu, intervensi eksternal berupa insentif moneter ataupun punishment justru berdampak negatif terhadap tax compliance (Battiston & Gamba, 2016;Christian, 2017;Feld & Larsen, 2012;Gangl, Torgler, Kirchler, & Hofmann, 2014;Güzel, Özer, & Özcan, 2019). Pajak merupakan hubungan kontraktual jangka panjang dan berulang antara WP dan otoritas pajak (Thornton & Shaub, 2014) dan beberapa penelitian telah membuktikan kerja sama pihak-pihak yang terlibat dalam sistem perpajakan berpengaruh terhadap kepatuhan WP (Alm, Cherry, Jones, & Mckee, 2010;Amponsah & Adu, 2017;Battison & Gamba, 2016;Castro & Scartascini, 2015;Eichfelder & Kegels, 2014;Lai, Yang, & Chang, 2003;Mohdali, Isa & Yusoff, 2014;Sipos, 2015;Vossler & McKee, 2017;Witherspoon & Stone, 2013). Ketika WP murni diperlakukan sebagai 'subjek' yang harus dipaksa untuk membayar pajak, WP cenderung merespon dengan melakukan penghindaran pajak (Williams & Horodnic, 2015); kontrak psikologis pajak antara WP dan petugas pajak berpengaruh terhadap tingkat tax moral yang membantu memecahkan masalah ketidakpatuhan (Ali & Ahmad, 2014).…”
Section: Gambar 3 Modifikasi Fischer's Modelsunclassified